2023
DOI: 10.1111/bjh.18690
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of early treatment of SARS‐CoV‐2 infection in patients with haematological disorders

Abstract: Outcome of early treatment of COVID-19 with antivirals or anti-spike monoclonal antibodies (MABs) in patients with haematological malignancies (HM) is unknown. A retrospective study of HM patients treated for mild/moderate COVID-19 between March 2021 and July 2022 was performed. The main composite end-point was treatment failure (severe COVID-19 or COVID-19-related death). We included 328 consecutive patients who received MABs (n = 120, 37%; sotrovimab, n = 73) or antivirals (n = 208, 63%; nirmatrelvir/ritonav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…In a retrospective series by the Gruppo Italiano Malattie Ematologiche dell'Adulto (GIMEMA group), Marasco et al reported on 91 haematological patients treated with different types of neutralizing anti‐Spike MABs, finding an incidence of hospitalization for COVID‐19 of 12% and a mortality rate of 3.3% 6 . In the retrospective series by Mikulska et al, the incidence of lung failure was 5.8% for patients treated with anti‐virals (remdesivir or oral anti‐virals NIR/r and MOL) and 11.8% for MABs 15 . Evaluating patients' characteristics, the study of the GIMEMA group presented patients predominantly with active and recently treated HM, a prevalent diagnosis of lymphoma, and a comparable median age and prevalence of patients after transplantation or CAR‐T therapy to our cohort, while patients' comorbidities for this study were not described.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a retrospective series by the Gruppo Italiano Malattie Ematologiche dell'Adulto (GIMEMA group), Marasco et al reported on 91 haematological patients treated with different types of neutralizing anti‐Spike MABs, finding an incidence of hospitalization for COVID‐19 of 12% and a mortality rate of 3.3% 6 . In the retrospective series by Mikulska et al, the incidence of lung failure was 5.8% for patients treated with anti‐virals (remdesivir or oral anti‐virals NIR/r and MOL) and 11.8% for MABs 15 . Evaluating patients' characteristics, the study of the GIMEMA group presented patients predominantly with active and recently treated HM, a prevalent diagnosis of lymphoma, and a comparable median age and prevalence of patients after transplantation or CAR‐T therapy to our cohort, while patients' comorbidities for this study were not described.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the retrospective series by Mikulska et al, the incidence of lung failure was 5.8% for patients treated with anti-virals (remdesivir or oral anti-virals NIR/r and MOL) and 11.8% for MABs. 15 Evaluating patients' characteristics, the study of the GIMEMA group presented patients predominantly with active and recently treated HM, a prevalent diagnosis of lymphoma, and a comparable median age and prevalence of patients after transplantation or CAR-T therapy to our cohort, while patients' comorbidities for this study were not described. Compared to the cohort reported by Mikulska et al, although the median age, number of comorbidities and distribution of HMs were similar to that of our study, 66.5% had received anti-cancer treatment and 12.8% HSCT or CAR-T therapy within 12 months of COVID-19, while the remaining patients had been out of therapy for longer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations